2004
DOI: 10.1177/0021998304040566
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar Stress Concentrations in Layered Structures: Part I - A Selective Literature Survey on the Free-Edge Effect since 1967

Abstract: Stress concentration phenomena in composite laminates are technically important situations. A well-known problem of this class is the free-edge effect in composite laminates or as a superordinated example the stress concentrations in the vicinity of free laminate corners (so-called free-corner effect). The present work is split into two parts. In the present contribution, after a short introduction to the given stress concentration problems in general we will survey relevant selected literature on the classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 113 publications
1
59
0
Order By: Relevance
“…three-dimensional crack [1][2][3] or notch [4] situations as well as stress ÿelds in the vicinity of free edges [5] and corners [6-8] of layered structures-by means of standard ÿnite element method (FEM) analyses is computationally quite involved. Thus, there is a particular interest in introducing new and e cient analysis methods like e.g.…”
Section: The Boundary Finite Element Methods (Bfem)mentioning
confidence: 99%
“…three-dimensional crack [1][2][3] or notch [4] situations as well as stress ÿelds in the vicinity of free edges [5] and corners [6-8] of layered structures-by means of standard ÿnite element method (FEM) analyses is computationally quite involved. Thus, there is a particular interest in introducing new and e cient analysis methods like e.g.…”
Section: The Boundary Finite Element Methods (Bfem)mentioning
confidence: 99%
“…The fracture mechanism of the joint is controlled by the stress concentration due to the contact angle and fiber compaction at the joint interface. It has been shown that all mechanical and adhesive composite joining methods impart some degree of stress concentration in the material [27,28]. Crack initiation and failure mechanisms at joint locations govern the macroscopic strength and failure of the composite [28,29].…”
Section: Bundle Joint Strengthmentioning
confidence: 99%
“…Examples of possible joining candidates include composite free edges [27], internal ply drop offs [29,31], holes [32] and between layers of lamina [33]. The potential for joining damaged fibers may also be of interest in the repair of composite structures after low velocity impacts [34].…”
Section: Seam Joint Strengthmentioning
confidence: 99%
“…[3]. Furthermore, we mention a general survey on the computation of interlaminar stress concentrations, see Mittelstedt and Becker [4]. In the following we would like to concentrate on the question how to calculate interlaminar stresses.…”
Section: Introductionmentioning
confidence: 99%